Patient-tailored adoptive immunotherapy with EBV-specific T cells from related and unrelated donors - Bonifacius A; Lamottke B; Tischer-Zimmermann S; Schultze-Florey R; Goudeva L; Heuft HG; Arseniev L; Beier R; Beutel G; Cario G; Frohlich B; Greil J; et al. (AMER SOC CLINICAL INVESTIGATION INC, 2025)
BACKGROUND.
Adoptive transfer of EBV-specific T cells can restore specific immunity in immunocompromised patients with EBV-associated complications.
METHODS.
We provide results of a personalized T cell manufacturing program evaluating donor, patient, T cell product, and outcome data. Patient-tailored clinical-grade EBV-specific cytotoxic T lymphocyte (EBV-CTL) products from stem cell donors (SCDs), related third-party donors (TPDs), or unrelated TPDs from the allogeneic T cell donor registry (alloCELL) at Hannover Medical School were manufactured by immunomagnetic selection using a CliniMACS Plus or Prodigy device and the EBV PepTivators EBNA-1 and Select. Consecutive manufacturing processes were evaluated, and patient outcome and side effects were retrieved by retrospective chart analysis.
RESULTS.
Forty clinical-grade EBV-CTL products from SCDs, related TPDs, or unrelated TPDs were generated for 37 patients with refractory EBV infections or EBV-associated malignancies with and without a history of transplantation, within 5 days (median) after donor identification. Thirty-four patients received 1-14 EBV-CTL products (fresh and cryopreserved). EBV-CTL transfer led to a complete response in 20 of 29 patients who were evaluated for clinical response. No infusion-related toxicity was reported. EBV-specific T cells in patients' blood were detectable in 16 of 18 monitored patients (89%) after transfer, and their presence correlated with clinical response.
CONCLUSION.
Personalized clinical-grade manufacture of EBV-CTL products via immunomagnetic selection from SCDs, related TPDs, or unrelated TPDs in a timely manner is feasible. Overall, EBV-CTLs were clinically effective and well tolerated. Our data suggest EBV-CTL transfer as a promising therapeutic approach for immunocompromised patients with refractory EBV-associated diseases beyond HSCT, as well as patients with preexisting organ dysfunction.
TRIAL REGISTRATION.
Not applicable.